Prototyping and modelmaking for product design - Hallgrimsson, Bjarki (London : Laurence King Publishing, 2020)
Building prototypes and models is an essential component of any design activity. Prototyping and Modelmaking for Product Design illustrates how prototypes are used to help designers understand problems better, explore more imaginative solutions, investigate human interaction more fully and test functionality so as to de-risk the design process. Following an introduction on the purpose of prototyping, specific materials, tools and techniques are examined in detail, with step-by-step tutorials and industry examples of real and successful products illustrating how prototypes are used to help solve design problems. Workflow is also discussed, using a mixture of hands on and digital tools. A comprehensive modern prototyping approach is crucial to making informed design decisions, and forms a strategic part of a successful designer's toolkit
First published in 2012
Includes bibliographical references and index
Keywords: Product design -- Planning; Prototypes, Engineering; Models and modelmaking